Economic Convergence across the Toba Lake Region - Sipahutar, Mangasa Augustinus (Quantitative Economics Research, 2019)
AbstractBased on the economic sectors, seven districts across the Toba Lake Region (TLR) has similar patterns in economic development ? agriculture, trade and construction are dominant economic sectors, however, there is an unconvergence economic growth across the TLR. It was found that the relationship between economic growth and unemployment in Toba and Dairi, and between economic growth and poverty in Toba, Dairi and Humbang can not be explained due to insignificant coefficient between economic growth to unemployment and poverty. Economic growth is not strong enough to reduce unemployment and poverty. It needs higher economic growth to influence of reducing both unemployment and poverty. In this case, dominant economic sectors in each district need a serious attention to promote higher growth that could significantly reduce unemployment and poverty. The highest strength of economic growth in reducing unemployment occurred in Simalungun which increasing economic growth by 1 per cent could reduce unemployment by 3,021 per cent, where in North Tapanuli, increase in economic growth by 1 per cent could reduce poverty by 4,534 per cent. Thus, the integration policies through prioritization of economic key drivers based on absolute advantage of each economic sector across the TLR is needed.Key words: economic convergence, economic growth, unemployment, povertyJEL Classification: O11; O21